Reconstruction of the early invasion history of the quagga mussel (Dreissena rostriformis bugensis) in Western Europe - Heiler, Katharina; Vaate, Abraham bij de; Ekschmitt, Klemens; Oheimb, Parm von; Albrecht, Christian; Wilke, Thomas; Justus Liebig University Giessen (My University, 2013)
The recent introduction of the quagga mussel into Western European freshwaters marked the beginning of one of the most successful biological invasions during the past years in this region. However, the spatial and temporal origin of the first invasive population(s) in Western Europe as well as subsequent spreading routes still remain under discussion. In this study, we therefore aim at reconstructing the early invasion history of the quagga mussel in Western Europe based on an age-corrected temporally and spatially explicit spread model. Data were derived from time-series studies at selected sites as well as from a broad spatial survey in Western Europe. According to our spread model, the first successful introduction into Western Europe occurred in the Main-Danube Canal in early 2004, probably via inland navigation. Once populations were established, subsequent spread of the quagga mussel was characterized by a combination of jump dispersal and diffusive spread. This study gives insights into the very early invasion history of the quagga mussel and stresses the importance of the Main-Danube Canal for the introduction of non-native freshwater species into Western Europe.
Keywords: ddc:570